ChemInform Abstract: A Straightforward Access to Guaiazulene Derivatives Using Palladium‐Catalyzed sp2 or sp3 C—H Bond Functionalization. Issue 39 (5th September 2013) - Zhao, Liqin; Bruneau, Christian; Doucet, Henri
Abstract A novel Pd‐catalyzed arylation of guaiazulenes (I) with aryl bromides (II) is reported.